Scientific and practical problems of creating an environmental code - Bogolyubov, Sergey A. (Journal of the Belarusian State University. Law, 2023)
Environmental legislation in a broad sense combines the natural resource and environmental parts. The natural resource part includes the land, forest, water codes, etc., the environmental part includes laws on environmental protection, on environmental expertise, on specially protected natural territories, etc. Options for its modernisation are being discussed, and this process faces considerable problems. More than three decades ago, the idea of drafting an environmental code was born. Its creation took several periods. The public had pinned their hopes on a new major specialised regulatory legal act. There were the difficulties in separating the environmental norms of the laws from their natural resource requirements. The resuscitation of attempts to create an environmental code in the third decade of the 21st century is due to the increasing threats of environmental degradation, increased responsibility of the state and society for the rational use of natural resources, environmental protection, turbulence of international relations, sanctions external pressure. When justifying a qualitatively new law, it is necessary objectively to take into account the state and development of environmental legislation, the level of application of legislative prescriptions, the role and differences of natural resource and environmental law, their structural parts in the system of legislation. Understanding the general and specific patterns of the creation of an environmental code should significantly improve environmental protection.
Keywords: improvement of environmental legislation; changes in the socio-economic situation; study of accumulated experience in drafting the environmental code; specific requirements for the creation of the code